Efficacy of azimsulfuron against complex weed flora in transplanted rice (Oryza sativa) under rainfed shallow lowland - SAHA, SANJOY; MUNDA, SUSHMITA; ADAK, TOTAN (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted during the wet seasons of 2010 and 2011 at ICAR-National Rice Research Institute, Cuttack to study the efficacy of azimsulfuron for controlling broad spectrum of weeds in transplanted rice (Oryza sativa L.) field under rainfed shallow lowland. The present study consisted of 10 treatments which includes seven doses of azimsulfuron, viz. 12.5, 17.5, 22.5, 27.5, 30.0, 35.0 and 40 g/ha each with 0.2% surfactant along with recommended herbicide, pretilachlor at 625 g/ ha, weed-free and weedy as check. Yield attributes of rice were significantly (P